Fogo selvagem: endemic pemphigus foliaceus - Günter Hans-Filho; Valéria Aoki; Nelise Ritter Hans Bittner; Guilherme Canho Bittner (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Fogo selvagem or endemic pemphigus foliaceus is an autoimmune acantholytic anti-cadherin bullous disease that primarily affects seborrheic areas, which might disseminate. Brazil has the world's largest number of patients, mainly in the Central-West region, but the disease has also been reported in other South American countries. It affects young people and adults who have been exposed to rural areas, with occurrence of familial cases. Anti-desmoglein-1 autoantibodies are directed against desmosomal structures, with loss of adhesion of the upper layers of the epidermis, causing superficial blisters. The etiology is multifactorial and includes genetic, immune, and environmental factors, highlighting hematophagous insect bites; drug-related factors are occasionally involved. Flaccid blisters readily rupture to yield erosive-crusty lesions that sometimes resemble seborrheic dermatitis, actinic keratosis, and chronic cutaneous lupus erythematosus. The clinical presentation varies from localized to disseminated lesions. Clinical suspicion should be confirmed with histopathological and immunofluorescence tests, among others. The progression is usually chronic, and therapy varies according to clinical presentation, but generally requires systemic corticosteroid therapy associated with adjuvant immunosuppressive treatment to decrease the adverse effects of corticosteroids. Once the disease is under control, many patients remain stable on low-dose medication, and a significant proportion achieve remission.